Respuesta :

   y - y₁ = m(x - x₁)
y - (-7) = -1¹/₅(x - (-3))
   y + 7 = -1¹/₅(x + 3)
   y + 7 = -1¹/₅(x) - 1¹/₅(3)
   y + 7 = -1¹/₅x - 3³/₅

[tex]m = \frac{y_{2} - y_{1}}{x_{2} - x_{1}} = \frac{-17 - (-2)}{3 - (-9)} = \frac{-17 + 2}{3 + 9}} = \frac{-15}{12} = \frac{-5}{4} = -1\frac{1}{4}[/tex]

   y - y₁ = m(x - x₁)
y - (-2) = -1¹/₄(x - (-9))
   y + 2 = -1¹/₄(x + 9)
   y + 2 = -1¹/₄(x) - 1¹/₄(9)
   y + 2 = -1¹/₄x - 11¹/₄
       - 2               - 2
         y = -1¹/₄x - 13¹/₄

   y - y₁ = m(x - x₁)
y - (-3) = ⁻¹/₄(x - 8)
   y + 3 = ⁻¹/₄(x) + ¹/₄(8)
   y + 3 = ⁻¹/₄x + 2
       - 3           - 3
         y = ⁻¹/₄x - 1

     y - y₁ = m(x - x₁)
y - (-17) = ¹/₂(x - (-6))
   y + 17 = ¹/₂(x + 6)
   y + 17 = ¹/₂(x) + ¹/₂(6)
   y + 17 = ¹/₂x + 3
       - 17          - 17
          y = ¹/₂x - 14

[tex]m = \frac{y_{2} - y_{1}}{x_{2} - x_{1}} = \frac{-4 - 8}{-4 - 6} = \frac{-12}{-10} = \frac{12}{10} = \frac{6}{5} = 1\frac{1}{5}[/tex]

y - y₁ = m(x - x₁)
 y - 8 = 1¹/₅(x - 6)
 y - 8 = 1¹/₅(x) - 1¹/₅(6)
 y - 8 = 1¹/₅x - 7¹/₅
   + 8            + 8
      y = 1¹/₅x + ⁴/₅
ACCESS MORE